Does Financial Literacy Improve Financial Inclusion? Cross Country Evidence - Antonia Grohmann; Theres Klühs; Lukas Menkhoff (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
While financial inclusion is typically addressed by improving the financial infrastructure, we show that a higher degree of financial literacy also has a clear beneficial effect. We study this effect at the cross-country level, which allows us to consider institutional variation. Regarding äccess to finance\", financial infrastructure and financial literacy are mainly substitutes. However, regarding the üse of financial services\", the effect of higher financial literacy strengthens the effect of more financial depth. The causal interpretation of these results is supported by IV-regressions. Moreover, the positive impact of financial literacy holds across income levels and several subgroups within countries.
Keywords: O01; G02; 330; financial inclusion; financial literacy; financial institutions; financial development